Twelve new species of Priceiella (Phthiraptera: Ischnocera: Philopteridae) from Old World babblers, with keys to species of two subgenera and checklists of species for the genus - Gustafsson, Daniel R.; Clayton, Dale H.; Bush, Sarah E. (Zootaxa, 2018)
Twelve new species of chewing lice in the genus Priceiella Gustafsson & Bush, 2017, are described from Old World “babblers” (Leiothrichidae, Paradoxornithiidae, Pellorneidae and Timaliidae). Eight species belong to the subgenus Thescelovora Gustafsson & Bush, 2017: Priceiella (Thescelovora) calcicola n. sp. from Turdinus crispifrons crispifrons; Priceiella (Thescelovora) fuscicaena n. sp. from Malacopteron magnum magnum and Malacopteron cinereum cinereum; Priceiella (Thescelovora) orichalca n. sp. from Turdinus brevicaudatus leucostictus and four other host species; Priceiella (Thescelovora) chanthaburiana n. sp. from Megapomatorhinus hypoleucos tickelli and Pomatorhinus schisticeps klossi; Priceiella (Thescelovora) macrocephala n. sp. from Megapomatorhinus hypoleucos wrayi; Priceiella (Thescelovora) coleyae n. sp. ex Stachyris striolata tonkinensis; Priceiella (Thescelovora) austini n. sp. ex Pomatorhinus ruficollis intermedius; and Priceiella (Thescelovora) ornata n. sp. ex Psittiparus gularis fokiensis. The remaining four species belong to the subgenus Camurnirmus Gustafsson & Bush, 2017: Priceiella (Camurnirmus) najeri n. sp. from Garrulax monileger stuarti and three other hosts; Priceiella (Camurnirmus) bohsae n. sp. from Garrulax strepitans; Priceiella (Camurnirmus) lindquistae n. sp. ex Ianthocincla chinensis chinensis; Priceiella (Camurnirmus) sonorae n. sp. ex Garrulax maesi maesi. We redescribe and illustrate Priceiella (Camurnirmus) rhinocichlae (Eichler, 1957). Keys to species of two subgenera, a comprehensive checklist of all the species of Priceiella, and a host-louse list are provided.